2005
DOI: 10.2174/1381612053381693
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and Cytokines Production - The Possible Cause of Gender Differences in Neurological Diseases

Abstract: Naturally occurring sexual dimorphism has been implicated in the risk, progression and recovery from numerous neurological disorders. These include head injury, multiple sclerosis (MS), stroke, and neurodegenerative diseases (Parkinson's disease (PD), Alzheimer's disease (AD) or amyotrophic lateral sclerosis (ALS). Accumulating evidence suggests that observed differences between men and women could result from estrogen's wide range of effects within the mammalian central nervous system (CNS), with it's neuropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
1
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 0 publications
4
63
1
2
Order By: Relevance
“…59,60 It was also argued recently that sex may play a more important role in brain structure and psychiatric disorders than commonly acknowledged. [61][62][63] Our finding is consistent with this converging evidence. Furthermore, our finding of sex-specific associations in CSF2RB is supported by molecular evidence.…”
Section: Discussionsupporting
confidence: 91%
“…59,60 It was also argued recently that sex may play a more important role in brain structure and psychiatric disorders than commonly acknowledged. [61][62][63] Our finding is consistent with this converging evidence. Furthermore, our finding of sex-specific associations in CSF2RB is supported by molecular evidence.…”
Section: Discussionsupporting
confidence: 91%
“…54,55 It was also argued recently that sex may play a more important role in brain structure and psychiatric disorders than commonly acknowledged. [56][57][58] Our finding is consistent with this converging evidence. Furthermore, our finding of sex-specific associations in this region has strong genomic and molecular basis, that is, the existence of EREs and other coordinating transcription factor binding sites in this region and the report of sex-specific expression of IL3 and ACSL6 genes.…”
Section: Discussionsupporting
confidence: 91%
“…Recent genome-wide studies have also identified single nucleotide polymorphisms in the IL-2 receptor alpha and IL-7 receptor alpha chains (The International Multiple Sclerosis Genetics Consortium, 2007), again indicating that genetic variations of immune response genes contribute to MS susceptibility. Women are affected by MS twice as frequently as men, which may be due to genetic or hormonal factors (Czlonkowska et al, 2005).…”
Section: Ms and Related Inflammatory Demyelinating Cns Diseasesmentioning
confidence: 99%